Aile Ev Dergisi ve Biyopolitika (1947-1952) - Odabaş, Sevim (FSM Vakıf Üniversitesi, 2019)
Bu yazı Türkiye’de biyopolitik mevzuların konuşulduğu kamusal metinlerden Aile Ev Dergisine odaklanmaktadır. Bu yazıda 1947-1952 yılları arasında aile, evlilik, kadınlık, çocukluk ve yaşam hakkında kamusal metin üreten Aile Ev Dergisinin monografisi sunulmaya çalışılmaktadır. Bu dergideki yazılar yahut kamusal metinler dönemin biyopolitik kaideleri ve mücadeleleri hakkında önemli noktalara dikkat çekmektedir. Didaktik, pedagojik bir üslupla okuyucularına modern hayat tarzı hakkında nasihatler vermektedir. Türkiye’de yurttaşların sahip olması gereken biyopolitik vasıflara işaret etmektedir.

This study focuses on Family Home Magazine, one of the public texts in which biopolitics issues are discussed. The study aims to present the monograph of Family Home Magazine produced public texts about family, marriage, womanhood, childhood and life between the years of 1947-1952. Articles or public texts in the magazine draw attention to the important points about biopolitics principles and struggles of the age. The magazine gives advices on modern lifestyle to its readers in a didactic and pedagogic way. It points out biopolitical qualifications that Turkish citizens must have.
Family Home Magazine and Biopolitics (1947-1952)
Keywords: Biyopolitika mevzuları; Aile; Evlilik; Çocukluk; Kadınlık; Biopolitics issues; Family; Marriage; Womanhood; Childhood